Mali I, Lopes - 10 Korriku - Theken - Terno ve chromite deposits and their potential - GJONI, V. (Bulletin of the Geological Society of Greece, 2001)
Mali Lopes-10 Korriku-Theken-Ternove chromite deposits are located in the Bulqiza ophiolite massif. According to the recent data, it is concluded that this area is a new very prospective target.